SEJARAH MASUKNYA ETNIS TIONGHOA DI SELATPANJANG KABUPATEN KEPULAUAN MERANTI - Ainun syarifatul alfiah; Ridwan Melay; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Ethnic is a community that displays language equation, customs, habit, region dan history characterized by the inner bond of its members. Chinese ethnicity is an individual who sees himself as a “Chinese” or is considered so by his environment ethnic Chinese originated from a region of China called Hokkien and then they became immigrants in a area in a area called Thailand and eventually the immgrants found Selatpanjang close to Singapore and Malaysia and settled there. The purpose of this research is (a) to find out about the entry of Chinese ethnic to Selatpanjang (b) to know the factors of ethnic Chinese arrival to Selatpanjang (c) to know the cultural mixing of Chinese society with local community in Selatpanjang (d) to know the response of local people about the existence ethnic Chinese in Selatpanjang. This research method is descriptive qualitative research procedurs that produce descriptive data in the form or written or oral words and behavior from people .That can be seen through the existence of temple Hoo Ann Kiong.Keywords: Ethnic Chinese, Selatpanjang